2013
DOI: 10.1371/journal.pone.0072371
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Predicting Blood Lead Levels in Pregnant Women in the UK: The ALSPAC Study

Abstract: BackgroundLead is a widespread environmental toxin. The behaviour and academic performance of children can be adversely affected even at low blood lead levels (BLL) of 5–10 µg/dl. An important contribution to the infant's lead load is provided by maternal transfer during pregnancy.ObjectivesOur aim was to determine BLL in a large cohort of pregnant women in the UK and to identify the factors that contribute to BLL in pregnant women.MethodsPregnant women resident in the Avon area of the UK were enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 44 publications
5
79
0
Order By: Relevance
“…One sample had a lead level below the limit of detection (0.29  μ g/dl): this sample was assigned a value of 0.7 times the lower limit of detection. The mean maternal B-Pb was 3.67 ± 1.47  μ g/dl ( n  = 4285; geometric mean 3.43, median 3.42, range 0.41–19.14  μ g/dl) 2. The birth outcomes are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One sample had a lead level below the limit of detection (0.29  μ g/dl): this sample was assigned a value of 0.7 times the lower limit of detection. The mean maternal B-Pb was 3.67 ± 1.47  μ g/dl ( n  = 4285; geometric mean 3.43, median 3.42, range 0.41–19.14  μ g/dl) 2. The birth outcomes are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The removal of lead from water pipes, paint and food cans, and a ban on lead additives to petrol in most countries has reduced exposure to lead in recent years, although industrial activities such as mining, smelting, lead shot manufacture and battery manufacture and recycling are still of concern. Food and drink, water, dust and soil remain as important sources of exposure,1 as does cigarette smoking 2,3…”
Section: Introductionmentioning
confidence: 99%
“…Bjermo et al (2013) have demonstrated meat intake to be inversely related to blood Cd concentrations. Smoking also contributes to increased blood Pb concentrations (Chelchowska et al, 2013;Taylor et al, 2013), and its uptake is found to be inversely related to Fe-stores (Mahaffey, 1990). Exposure of the general population to Pb has been linked to multiple sources including: dietary (e.g., consumption of foods grown on contaminated soils, some wines, hunted game and waterfowl and the associated use of leaded ammunition); leaded paints; contaminated soils and air; and certain hobbies such as making Pb sinkers Meltzer et al, 2013;Hanning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Human biomonitoring (HBM) provides a more direct measure of actual personal exposure to environmental chemicals, but interpretation can be limited due to a lack of UK population based reference levels to compare with. There are some health-based projects that have contributed to the understanding of environmental chemical exposures in the UK population, such as the Avon Longitudinal Study of Parents and Children (ALSPAC), which has published, for example, on lead and mercury exposures in pregnancy Taylor et al 2013). A study for the UK population by Bevan and colleagues collected data to develop reference ranges for a number of environmental chemicals in widespread use including benzene, cadmium, mercury and naphthalene (Bevan et al 2013).…”
Section: Introductionmentioning
confidence: 99%